Shrink the Targets. - Perrow, C.
Charles Perrow, professor emeritus of sociology at Yale University, expresses his views on fighting global terrorism. Perrow believes that governments should focus on defending against natural calamities and industrial accidents, which are more frequent and disastrous threats. By defending against these eventualities, the damages from terrorist attacks can also be mitigated. Perrow further suggests that instead of protecting big targets, governments should reduce them to make them less consequential and easier to protect
Keywords: Disastrous threats; Global terrorism; Industrial accidents; Natural calamities; Terrorist attacks